ANALISIS PENGGUNAAN BAHASA DAERAH DAN BAHASA BAKU DALAM FILM LASKAR PELANGI - Putria, Najhwa Tsalisa; Natasya, Aisya Meidina; Sahara, Finanda Adnin; Cahya, Anggun Amanda Wulan; Muasomah; Abdul Mukhlis (JBI : Jurnal Bahasa Indonesia, 2025)
This study aims to analyze the use of regional languages and standard languages in the film Laskar Pelangi, focusing on the characteristics, functions, and contributions in conveying the message of the story adapted from the novel by Andrea Hirata. The method used is descriptive   qualitative with data collection techniques through direct hearing the dialogue of the characters in the film. The results of the analysis showed that regional languages, especially the Belitung Malay dialect, are used authentically in everyday conversations to strengthen cultural identity, create emotional closeness, and represent the social reality of the local community. Meanwhile, standard Indonesian is used in formal contexts, especially in educational interactions between teachers and students, making it effective in conveying educational and moral messages. The combination of these two languages not only enriches the meaning of the story and reinforces the film's message about the importance of Education, unyielding spirit, and cultural preservation, but also reflects the dynamics of Indonesia's multicultural and bilingual society. Thus, the use of language in this film can be used as a reference in language and literature learning in the world of education, as well as showing the depth of the culture of local communities represented through literary works and films.